1986
DOI: 10.1073/pnas.83.3.546
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and organization of the human protein C gene.

Abstract: We have isolated overlapping phage genomic clones covering an area of 21 kilobases that encodes the human protein C gene. The gene is at least 11.2 kilobases long and is made up of nine exons and eight introns. Two regions homologous to epidermal growth factor and transforming growth factor are encoded by amino acids 46-91 and 92-136 and are precisely delimited by introns, as is a similar sequence in the genes for coagulation factor IX and tissue plasminogen activator. When homologous amino acids of factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(100 citation statements)
references
References 34 publications
1
96
0
3
Order By: Relevance
“…5,6 The human PC gene maps to chromosome 2q13-q14, 7 spans over 11 kb, and comprises a coding region (exons II to IX) and a 5Ј untranslated region encompassing exon I. 8,9 Three polymorphic sites (-1654 C/T, -1641 A/G, and -1476 A/T) are located in the 5Ј nontranscribed region of the PC gene. In 44 unrelated individuals in whom familial studies could be performed, 3 of 8 possible haplotypes (CGT, TAA, and CAA) were observed with frequencies of 0.33, 0.30, and 0.25, respectively.…”
mentioning
confidence: 99%
“…5,6 The human PC gene maps to chromosome 2q13-q14, 7 spans over 11 kb, and comprises a coding region (exons II to IX) and a 5Ј untranslated region encompassing exon I. 8,9 Three polymorphic sites (-1654 C/T, -1641 A/G, and -1476 A/T) are located in the 5Ј nontranscribed region of the PC gene. In 44 unrelated individuals in whom familial studies could be performed, 3 of 8 possible haplotypes (CGT, TAA, and CAA) were observed with frequencies of 0.33, 0.30, and 0.25, respectively.…”
mentioning
confidence: 99%
“…Residues 134-143 in trypsin or 148-157 in chymotrypsin, homologous to residues 3 11-320 in PC (Table l), form an exposed loop on the surface of the catalytic domain, whereas trypsin residues 144-148 or chymotrypsin 159-162, homologous to 321-325 in PC, are rather buried in the structure. "Amino acids in PC are numbered according to Plutzky et al (1986). Sequence alignment was performed as described (Mesters et al, 1991) with the additional alignment of the sequences of bovine PC (Fernlund & Stenflo, 1982;Stenflo & Fernlund, 1982) and bovine trypsinogen (Mikes et al, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The human gene encoding PC (PROC) is located on the long arm of chromosome 2 (2q13-q14) and contains 9 exons that code for 461 amino acid residues [3,4]. The human PS gene (PROS1) resides on chromosome 3 (3p11.1-q11.2) and contains 15 exons coding for 636 amino acid residues [5][6][7].…”
Section: Introductionmentioning
confidence: 99%